Graphical representation of place in conservatory tourism design / Thirathep (Tom) Chonmaitree - Chonmaitree, Thirathep (Tom) (Universiti Teknologi MARA, 2020)
In the city of ancient history for hundreds of years, Banglumphu as a historical tourism site has been promoted to be a popular tourist destination in Bangkok. Tourism businesses come along and eradicate some part of historical architecture and the local's way of life. Using traditional and digital media to convey the story of Banglumphu can be a challenge. Evaluating the sense of place from its architecture, religion, communities, and gastronomic categories and using them for media design in delivering a significant message of long history could stimulate historical tourism in learning the real Banglumphu. Photographic surveys and interviews are used to discover the history of the area as primary research alongside literature research. The shape of place identity in each category for this study has been used in developing the design. The meaning of shape delivers place memory and place attachment to the tourists to recognize Banglumphu with their impressive stay. The marketing media and map of attraction place based on the history known to the locals hopefully enhances tourist discovery of Banglumphu as a historical site and triggers their good memory after a visit.